2014
DOI: 10.1039/c3nr06160d
|View full text |Cite
|
Sign up to set email alerts
|

Cu2−xSe@mSiO2–PEG core–shell nanoparticles: a low-toxic and efficient difunctional nanoplatform for chemo-photothermal therapy under near infrared light radiation with a safe power density

Abstract: A low-toxic difunctional nanoplatform integrating both photothermal therapy and chemotherapy for killing cancer cells using Cu₂-xSe@mSiO₂-PEG core-shell nanoparticles is reported. Silica coating and further PEG modification improve the hydrophilicity and biocompatibility of copper selenide nanoparticles. As-prepared Cu₂-xSe@mSiO₂-PEG nanoparticles not only display strong near infrared (NIR) region absorption and good photothermal effect, but also exhibit excellent biocompatibility. The mesoporous silica shell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 48 publications
0
59
0
Order By: Relevance
“…[27] All the above results clearly revealed that both acidic pH and NIR can facilitate the releaseo fD OX to achieve the dual-stimuli responsive controlled release, which could dramatically improve the therapeutice fficacy and reduce side effects.…”
Section: Resultsmentioning
confidence: 89%
“…[27] All the above results clearly revealed that both acidic pH and NIR can facilitate the releaseo fD OX to achieve the dual-stimuli responsive controlled release, which could dramatically improve the therapeutice fficacy and reduce side effects.…”
Section: Resultsmentioning
confidence: 89%
“…Meanwhile, PTT combined with chemotherapy to achieve synergistic treatment manner, [11][12][13] which not only enhances the cell's uptake of the drug, but also controls the triggering of the release of drug molecules from drug carriers. A variety of NIR photo-absorbing agents have received a new discovery in the PTT including two-dimensional transition metal sulfide (MoS 2 and WS 2 ), [14] nonstoichiometric metal chalcogenides (WOx, Cu 2-x Se, Cu 2-x S), [15][16][17][18] noble metal (Au, Pt) nanomaterials, [19][20][21] carbon-based nanomaterials, [22][23][24][25][26] conducting polymers, [27] and so on. Nowadays, the discoveries of localized surface plasmon resonance (LSPR) nanomaterials have gradually attracted the attention of the scientific community.…”
Section: Introdutionmentioning
confidence: 99%
“…In particular, the development of nanomedicine approaches to treat cancer metastasis has received significant attention in these years . Different from conventional chemotherapy, which exhibits severe toxic effect and may easily induce drug‐resistance, photothermal therapy (PTT) as recently developed cancer treatment strategy is able to selectively ablate tumors using near‐infrared (NIR) light absorbing nanoagents with minimal damage to normal tissues . In our previous studies, it has been found that several types of NIR light absorbing nanoagents after being injected into the solid tumors would migrate by passive diffusion to the nearby SLNs, which then could be effectively ablated under NIR light‐triggered PTT .…”
mentioning
confidence: 99%